2006
DOI: 10.1889/1.2196511
|View full text |Cite
|
Sign up to set email alerts
|

LTPS circuit integration for system‐on‐glass LCDs

Abstract: A 3.5-in. QVGA-formatted driving-circuit fully integrated LCD has been developed using low-temperature poly-Si (LTPS) technology. This display module, in which no external ICs are required, integrates all the driving circuits for a six-bit RGB digital interface with an LTPS device called a "FASt LDD TFT" and achieves a high-quality image, narrow frame width, and low power consumption. The LTPS process, device, and circuit technologies developed for system-on-glass LCD discussed. The development phase of LTPS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is observed that even V T shift happens, by the end of every conversion procedure, V M can still be fully charged. As a result, V O can be generated according to (1). However, if ΔV T is increased to 5V, the charging time for V M becomes insufficient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that even V T shift happens, by the end of every conversion procedure, V M can still be fully charged. As a result, V O can be generated according to (1). However, if ΔV T is increased to 5V, the charging time for V M becomes insufficient.…”
Section: Resultsmentioning
confidence: 99%
“…System on panel (SoP) has attracted enormous attentions in FPD field due to potentially enabling a significant improvement on performance, cost and reliability [1], [2]. The primary stage of fulfilling the SoP is the implementation of the integrated scan and data drivers with TFT technology.…”
Section: Introductionmentioning
confidence: 99%
“…To lower the assembly cost and reduce the display form factor, the trend is to integrate the peripheral circuits and the TFT array on the same substrate (usually glass). Recently, system-on-panel displays with built-in drivers and even the control and timing circuits have been reported [8], [9], [10], [11]. While these highly integrated systems have reduced form factors and enhanced robustness, they pose new challenges to array testing.…”
Section: A Tft Array Testingmentioning
confidence: 99%
“…Since low temperature poly-Si (LTPS) thin film transistors (TFTs) were introduced, many researches on system-on-glass (SOG) have been conducted due to high mobility of around 100 cm 2 /V s, where gate drivers, source drivers, timing controller, power circuits, memories, and sensors have been integrated on a glass [1][2][3][4]. However, at present, only gate drivers have been embedded in mass-produced active matrix flat panel displays with amorphous Si, LTPS, and oxide TFTs because they can be implemented with relatively simple and small-size digital circuit techniques compared to other circuits [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%